DESIGN OF NETWORK-BASED SECURITY SYSTEM FOR WINDOWS NT NETWORK OPERATIONS TO ACHIEVE EFFICIENCY - Sutono Sutono; Drs. Lingga Hermanto, MM Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 1999)
In building a network of points that a lot of attention is on the network operatingsystem installation and implementation of network security systems and maintenanceof existing network systems. Data security is very important but because it provideswindows applications security system that can protect applications that are used bythe user that is using the mandatory profile and policy editor. a user is restricted tolimit the network but also users can create security on the local drive directory is usedso it can not be accessed by anyone, including supervisors.